Bidirectional effect modifications of temperature and PM2.5 on myocardial infarction morbidity and mortality in Beijing, China from 2007 to 2021 - Piaopiao Hu; Qinghui Zeng; Jie Chang; Moning Guo; Feng Lu; Yue Qi; Zhao Yang; Pingping Jia; Qiuju Deng; Jing Liu (Ecotoxicology and Environmental Safety)
Background: Ambient temperatures and PM2.5 can trigger myocardial infarction (MI), while little is known about the complex interplay between these two factors on MI, especially morbidity. Objectives: To investigate bidirectional effect modifications of temperature and PM2.5 on MI morbidity and mortality. Methods: A time-stratified case-crossover study was conducted utilizing high-resolution data of temperature and PM2.5, along with 498,077 MI cases from the citywide registry in Beijing, China from 2007 to 2021. A conditional logistic regression model combined with a distributed lag non-linear model was used to examine linear and categorical effect modifications of temperature and PM2.5 on MI morbidity and mortality. Results: The PM2.5 effect on MI morbidity, modified by temperature, showed a progressive increase of odds ratio from 1.013 (95 % CI: 1.001, 1.025) to 1.027 (95 % CI: 1.012, 1.042) with rising temperatures. Stratified analysis revealed a greater PM2.5 effect in high temperature strata (1.049, 95 % CI: 1.029, 1.069) compared with low strata (1.007, 95 % CI: 0.993, 1.021) on MI morbidity (PZ test<0.001). The temperature effect on MI morbidity was also modified by PM2.5, with a gradual upward risk trend observed with increasing PM2.5 concentration. Specifically, the heat wave effect was greater at high PM2.5 concentration strata (1.097, 95 % CI: 1.042, 1.155) than at low strata (0.954, 95 % CI: 0.890, 1.023) (PZ test=0.002). The cold spell effect was greater at high PM2.5 concentration strata (1.181, 95 % CI: 1.117, 1.249) than at low strata (0.883, 95 % CI: 0.740, 1.053) (PZ test=0.002). A similar bidirectional effect modification of temperature and PM2.5 was also found in MI mortality. Conclusions: Temperature and PM2.5 bidirectionally modify their effect on MI morbidity and mortality. Elevated temperatures exacerbate PM2.5 effect, while increased concentrations of PM2.5 amplify temperature effect. The combined effect of temperatures and PM2.5 should be stressed, encompassing not only extreme conditions but also the entire range of exposures.